Twelve Days at Nuku Hiva Russian Encounters and Mutiny in the South Pacific - Govor, Elena (University of Hawaii Press, 2010)
In August 1803 two Russian ships, the Nadezhda and the Neva, set off on a round-the-world voyage to carry out scientific exploration and collect artifacts for Alexander I's ethnographic museum in St. Petersburg. Russia's strategic concerns in the north Pacific, however, led the Russian government to include as part of the expedition an embassy to Japan, headed by statesman Nikolai Rezanov, who was given authority over the ships' commanders without their knowledge. Between them the ships carried an ethnically and socially disparate group of men: Russian educated elite, German naturalists, Siberian merchants, Baltic naval officers, even Japanese passengers. Upon reaching Nuku Hiva in the Marquesas archipelago on May 7, 1804, and for the next twelve days, the naval officers revolted against Rezanov's command while complex crosscultural encounters between Russians and islanders occurred.